Enhancing Adolescent Nutrition Knowledge Through Digital Innovation: Evaluating the Effectiveness of E-Pocket Books in Reducing Obesity - Hastuti, Puput Tri; Utami, Siti Budi; Rialihanto, Muhammad Primiaji; Susilo, Joko; Attawet, Jutharat; Siswati, Tri (Health Dynamics, 2025)
Background: Balanced nutrition education is an essential effort in preventing obesity, especially in adolescents who are vulnerable to nutritional problems due to unhealthy diets and a lack of knowledge. This study aims to determine the effectiveness of Android-based e-pocket books in improving the understanding of balanced nutrition among adolescents in Yogyakarta. Methods: This study employed an experimental design with control groups, utilizing pre-tests and post-tests. Conducted from February to March 2023 in a high school in Yogyakarta, Indonesia, the research established a minimum sample size of 27 students per group through the Lemeshow formula and multistage sampling. Inclusion criteria required students to have Android phones, to consent to participate, to attend the study, and to complete data collection. The treatment group received education via e-pocket-book media, while the control group used e-leaflets. Knowledge was measured at three points: before the intervention, immediately after (post-test 1), and nine days later (post-test 2). Data analysis was performed using the Wilcoxon and Mann-Whitney tests with SPSS software. Results: The knowledge score of the treatment group increased from 76.3 (pre-test) to 93.8 (post-test 1) and 91.3 (post-test 2). The control group increased from 73.8 (pre-test) to 82.5 (post-test 1) and 81.3 (post-test 2). The increase in knowledge was more significant in the treatment group, showing that e-pocket-books were more effective than e-leaflets. Conclusion: Android-based e-pocket-books improve adolescents' knowledge of balanced nutrition more than e-leaflets. Digital technology in nutrition education has great potential to be applied in schools. Further research is needed to evaluate the long-term impact on nutritional behavior.